The Initial Conditions for Planet Formation: Turbulence Driven by Hydrodynamical Instabilities in Disks around Young Stars. (12th June 2019) - Lyra, Wladimir; Umurhan, Orkan M.
Abstract: This review examines recent theoretical developments in our understanding of turbulence in cold, non-magnetically active, planetesimal-forming regions of protoplanetary disks that we refer to throughout as "Ohmic zones." We give a brief background introduction to the subject of disk turbulence followed by a terse pedagogical review of the phenomenology of hydrodynamic turbulence. The equations governing the dynamics of cold astrophysical disks are given and basic flow states are described. We discuss the Solberg–Høiland conditions required for stability, and the three recently identified turbulence-generating mechanisms that are possibly active in protoplanetary disk Ohmic zones: (i) the vertical shear instability, (ii) the convective overstability, and (iii) the zombie vortex instability. We summarize the properties of these processes, identify their limitations, and discuss where and under what conditions these processes are active in protoplanetary disk Ohmic zones.